Ranking of serving policies with simulations of indirect access warehouse - Hartványi, Tamás; Nagy, Zoltán András; Szabó, Miklós (Advanced Logistic Systems - Theory and Practice, 2024)
The efficiency of warehouse processes is influenced by the design, layout and operation of the warehouse. We have developed a simulation process to valuate how the initial arrangement of products affects logistics activities in an inhomogeneous storage environment with no direct access. Continuing our research, we compared the operational logics commonly used in warehouses with indirect storage access through that simulation. The results were classified using a complex evaluation method, and then the ranking of the service logics was established. We believe that our research results can be useful for all those who want to achieve a more efficient use of warehouse space while respecting service time limits.